Thermogravimetric Analysis of EFB and Palm Shells as Gasification Fuels: Kinetic and Activation Energy Study - Ria Komala; Dedi Rohendi; Fakhili Gulo; Muhammad Faizal (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Solid waste from palm oil industry such as EFB and palm kernel shells pose environmental challenges if not properly managed. This study investigated the thermal characteristics and decomposition kinetics of EFB and palm kernel shells through proximate analysis and thermogravimetric analysis (TGA). The results indicate that palm kernel shells have a greater fixed carbon content (21.03–21.35%) than does EFB (19.60–20.06%), whereas EFB has a greater ash content (4.74–5.38%) than does palm kernel shells (1.25–1.31%). EFB showed a weight loss of 94.67% after 233.33 minutes of heating, whereas it was 99% for the palm kernel shells. The peak temperatures reached were 936.67 °C for the EFB and 930 °C for the palm kernel shells. At 600°C, EFB produced more syngas than palm kernel shells did. The calculated activation energies were 4482.19 J/mol for EFB and 4484.97 J/mol for palm kernel shells. This research enhances the understanding of the gasification efficiency of these materials, aiding in the optimization of eco-friendly energy production.Keywords: Empty fruit bunches, palm kernel shells, activation energy, thermogravimetric analysis, gasification